The PENGARUH E-COMMERCE ADOPTION, DAN INNOVATION TERHADAP BUSINESS PERFORMANCE YANG DIMEDIASI OLEH TRUST (STUDI KASUS: PERUSAHAAN KELUARGA DI INDONESIA) - Mizell Jocasta; Helena Sidharta (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
The internet has revolutionized how people shop and interact with businesses. This transformation has created significant opportunities for small and medium-sized enterprises (SMEs), including family businesses, to enhance their business performance. Some strategic actions that business owners can take include adopting e-commerce to keep up with technological developments and fostering innovation to stay relevant in a rapidly changing environment. Moreover, innovation has been proven to improve business performance through developing goods and offerings that more effectively address consumer demands, increasing process efficiency, and opening new opportunities for business model development. The urgency of this research lies in the fact that family businesses—one of the most dominant business forms in Indonesia—face major challenges in adapting to these changes. The goal of this investigation is to address this shortfall by analyzing the impact of adopting e-commerce and innovation on improving business performance, as well as assessing the role of trust as a mediating variable. The study employs the Structural Equation Modelling (SEM) method based on Partial Least Squares (PLS) to analyze responses from 62 participants who met the research criteria. The research indicates a beneficial link between e-commerce, innovation, and overall business success. Additionally, the study identifies a positive influence of e-commerce on trust. On the other hand, the outcomes suggest no notable positive link between trust and business performance, and trust doesn't mediate the connection between e-commerce and business performance.